A Simple and Compact Transimpedance Mode dc Bridge Readout - Seangrawee Buakaew; Wipavan Narksarp; Chariya Wongtaychatham (My University, 2021)
This paper presents a new circuit configuration of a transimpedance mode dc bridge based on an operational transresistance amplifier (OTRA) as an analog building block. The proposed circuit suits for small changing resistance detector. By taking the benefit of grounding property at the internal input port of the OTRA, a simple and compact dc bridge is obtained. The proposed circuit is composed of two sensing components together with a feedback resistor and only one operational transresistance amplifier. The circuit performances are verified by the PSPICE simulation using 0.35 μm CMOS technology model parameters. The simulation results from circuit level agree well with the theoretical values.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in Semiconductor Devices and Circuit Design; Electrical and Bioimpedance Tomography